Excel Success One HSC Business Studies : Past HSC Papers & Detailed Answers 2001-2010 With Topic Index : Plus Mark Maximizer Guide - Pascal Press (Glebe, NSW Pascal Press, 2011)
Designed to maximize your mark in the HSC by giving you essential practice at answering the types of questions you can expect
Keywords: New South Wales -- Business -- Business--Study and teaching (Secondary)